Research Handbook on Climate Change Adaptation Policy - Poto, Margherita Paola (Arctic Review on Law and Politics, 2019)
The Research Handbook on Climate Change Adaptation Policy... is a collection of contributions on the theme of climate change adaption policies... [T]he contributors offer a unique bird’s eye view from the perspective of 14 countries: Australia, Austria, Canada, Finland, France, Germany, Kenya, the Netherlands, New Zealand, Norway, Singapore, Sweden, the U.K. and the U.S.A....